2018
DOI: 10.2516/ogst/2018019
|View full text |Cite
|
Sign up to set email alerts
|

An improved modeling approach for asphaltene deposition in oil wells including particles size distribution

Abstract: There are several approaches to model asphaltene deposition process in the wellbore. There are different assumptions to simplify the problem in the previous investigations for specific conditions, limiting the prediction range of the models. In this work, the effect of precipitated asphaltene particles size is included, to extend the available modeling approaches for deposition profile. To do so, two-dimensional partial differential equations based on asphaltene micro aggregates material balance including asph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It can be seen from Figure 10 that, the crystal structure of Akshabulak oil at 5°C without EVA is much larger than crystal structures of oil when we applied EVA and EVA-M. Moreover, Akshabulak oil at 5°C easily solidified without adding any additives due to formation of various shapes of wax depositions [25,26]. According to studies the morphology of the crystal structures of paraffins after the addition of modified EVA it should be concluded that the formation of plate-like structures is due to repellent of wax crystals by the polar acetate group in EVA copolymer that prevent the formation of large agglomerates of Table 7.…”
Section: Influence Of Modified Ppd On Transition Of Waxy Crude Oils Fmentioning
confidence: 98%
“…It can be seen from Figure 10 that, the crystal structure of Akshabulak oil at 5°C without EVA is much larger than crystal structures of oil when we applied EVA and EVA-M. Moreover, Akshabulak oil at 5°C easily solidified without adding any additives due to formation of various shapes of wax depositions [25,26]. According to studies the morphology of the crystal structures of paraffins after the addition of modified EVA it should be concluded that the formation of plate-like structures is due to repellent of wax crystals by the polar acetate group in EVA copolymer that prevent the formation of large agglomerates of Table 7.…”
Section: Influence Of Modified Ppd On Transition Of Waxy Crude Oils Fmentioning
confidence: 98%
“…Changes in pressure, temperature, composition and sliding velocity can lead to the deposition of asphaltenes and the accumulation of deposits [2,3]. These changes can occur due to various processes, such as primary depletion, injection of natural or carbon dioxide (Gas injection is one of the main types of enhanced oil recovery (EOR) methods), acid treatment or coproduction of incompatible fluids.…”
Section: Asphaltene Formation and Depositionmentioning
confidence: 99%
“…Therefore, during the waterflooding process, they are mostly attracted to the oil/water interface and form a rigid film that prevents the water droplet coalescence. This process can lead to stable emulsion formation, asphaltene instability, and deposition. , Moreover, asphaltene particles could adsorb and deposit on the reservoir rock surface and alter the rock wetting state to oil-wet conditions, causing pore plugging and injectivity/productivity decline. , …”
Section: Introductionmentioning
confidence: 99%